Prioritising Lean Construction Barriers In Uganda's Construction Industry - Alinaitwe, Henry Mwanaki (Penerbit Universiti Sains Malaysia, 2009)
Engaging in lean construction efforts could prove to be highly rewarding for building firms in Uganda. However, lean construction is risky and can be disastrous if not properly managed. Lean production efforts in some other countries have not been successful due to the many barriers to its successful implementation. To enable sound lean construction efforts and to increase the chances of success in eliminating waste, a thorough investigation of the barriers is essential. This study presents 31 barriers and investigates their influence (strength) on the success of lean construction initiatives. Structured interviews were carried out with technical managers of building firms to assess their perception of the barriers to lean production based on their experience at their firms. The strongest barrier is the provision of inputs exactly when required. Additionally, the barriers were ranked according to the ease of overcoming each. The easiest barrier to overcome is keeping the required items in the right place. Finally, a graphical aid is provided to enable decision makers to concentrate their efforts on the influential (strong), yet easy to overcome barriers. A lack of buildable designs and a participative management style for the workforce are the most important barriers to successful waste reduction in terms of strength and ease of overcome. On the other hand, a lack of an organisational culture that supports teamwork, a lack of prefabrication and a lack of knowledgeable and skilled workers are regarded as low in strength, and at the same time difficult to overcome.